Ultrasound-guided microwave ablation for benign thyroid nodules results in earlier and faster nodule shrinkage in patients with Hashimoto's thyroiditis than in those with normal thyroid function - Chen, Yihao; Liu, Weizong; Jin, Chunchun; Xu, Xiaohong; Xu, Lifeng; Lu, Jianghao; Zheng, Jing; Sun, Xiangmei; Feng, Jiaping; Chen, Sihan; Li, Zhengyi; Gong, Xuehao (Frontiers in Surgery, 2023)
Objectives: Given that the histological features of the thyroid parenchyma in patients with Hashimoto's thyroiditis (HT) differ from those of the normal thyroid gland, HT may affect the effectiveness of ultrasound-guided microwave ablation (MWA) for benign thyroid nodules (BTNs). The present study aimed to compare the effectiveness of MWA for the treatment of BTNs in patients with both BTNs and HT and those with BTNs and normal thyroid function, based on changes in the volume reduction ratio (VRR) of the BTNs. Methods: Patients who had achieved a VRR ≥50% after MWA for BTN (July 2020–June 2021), followed up for 12 months, and their data were retrospectively analyzed. Results: A total of 213 nodules were identified in 185 patients, including 167 in the “BTN” group and 46 in the “BTN+HT” group. A comparison of the fitting curves for VRR–follow-up time revealed that the VRR increased with time after MWA, although the relationship was nonlinear. Piece-wise linear regression model analysis of the threshold effect of VRR and follow-up time in the two groups indicated that the inflection point of the “BTN” group occurred at 2.1 months: VRR increased fastest within 2.1 months of MWA (rate of change: 32.9% per month; P<0.001), following which the rate of change was slower and maintained at 1.0% per month (P=0.006). In the “BTN+HT” group, the inflection point occurred 1.5 months after MWA, with the most significant increase occurring in this period (rate of change: 41.5% per month; P<0.001), followed by a rate of 2.8% per month (P<0.001) after 1.5 months. Conclusions: The relationship between VRR and follow-up time for ultrasound-guided MWA for BTN is nonlinear and exhibits a threshold effect. The current results indicated that the VRR in both groups increased before and after the inflection point, although the rate of change was greater before than after the inflection point. The inflection point occurs earlier in patients with BTN+HT than in those with BTN yet normal thyroid function, and this difference may be related to the “oven effect” involved in the development of HT.